Anti-human trafficking laws in Malaysia - Ab Hamid, Zuraini (IIUM Press, International Islamic University Malaysia, 2017)
Human trafficking is a modern day slavery which becomes a global phenomenon and poses a real threat in all countries including Malaysia. The heinous crime is by nature a transnational organized crime, the commission of which cuts across national borders. Many researchers and policy makers from various countries have put their best effort in understanding the crime. However, the lack of resources particularly in Malaysia has put this effort in difficulty. Researchers need to spend a lot of time to gather the information from the relevant individuals. They faced difficulties when dealing with the government officers due to their duty of secrecy. Therefore, the principal objective of this book is to examine the Malaysian legal framework on human trafficking. A few selected cases of human trafficking in Malaysia will also be examined. The examination of these cases is necessary in order to identify the pattern of judicial decisions for human trafficking cases in Malaysia. Meanwhile, the laws of human trafficking in Australia shall be referred to compare legislative approaches taken by Malaysia and in fighting against human trafficking. This book found that there are significant problems with the Malaysia legal framework and its enforcement in dealing with the crime which contributes to the country’s downgrade to Tier 3 in 2014 from its previous ranking as a Tier 2 Watch List country, in Trafficking in Persons reports 2011 to 2013, provided by the US Department of State. The methodology utilised is fieldwork research which data was gathered from government enforcement and legal officers, together with published printed sources. All research data are supported by statistical data and cases obtained from the authority and reliable sources. In addition, it will enhance the academia world where the lecturers and students will have a reference on the issue since it has been introduced in their academic syllabus such as at UKM and IIUM for criminal law subject. They will have a better understanding on the ATIPSOM 2007 and other supplementary acts that relevant to the issue.